Food Blog Found on Love and Lemons Blogger: Corpus Analysis of Culinary Linguistics - Aldiansyah, Muhammad Givahri; Sari, Winda Setia (LINGUISTIK TERAPAN, 2024)
This study aims to determine the lexical items, food blogs, and hedges found on Love and Lemons bloggers using the AntConc corpus application based on Crystal and Diemer & Frobenius' theory. This research method uses mixed-method qualitative and quantitative data. The data source for this research was taken from the two most viewed recipes from the Love and Lemons blog entitled breakfast sandwiches and healthy breakfast tacos. This study focuses on the frequency of occurrence of lexical items, hedges and the use of food jargon found in recipes for breakfast sandwiches and breakfast healthy tacos. The results of this study indicate that lexical items found in Breakfast Sandwich (106), modification breakfast sandwich (13), evaluation breakfast sandwich (12) and hedges breakfast sandwich (7). While the classifications of lexical items found in recipe Breakfast Healthy Tacos (47), modification breakfast healthy tacos (13), evaluation breakfast healthy tacos (12), Hedges Breakfast Healthy Tacos (6). Based on the results the lexical contained in the Love and Lemons blog is widely used in the process of making healthy breakfast sandwiches and breakfast tacos. Based on Crystal theory found (8) types of food and (9) connotes of food from recipe breakfast sandwich and (12) types of food, (8) connotes of food from recipe breakfast healthy tacos. Food jargon terms are often used in food processing and food recipes in breakfast sandwich recipes and healthy breakfast taco recipes. Use hedging on the Love and Lemons blog to express a lack of certainty or caution in presenting readers with additional choices or options about which recipe to mix.